2008
DOI: 10.1002/pi.2520
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrophobic monomer on the synthesis and swelling behaviour of a collagen‐graft‐poly[(acrylic acid)‐co‐(sodium acrylate)] hydrogel

Abstract: BACKGROUND: Graft polymerization of vinylic monomers onto natural backbones is an efficient approach for the synthesis of natural-based superabsorbents. The nature of the monomers will affect the swelling behaviour of the superabsorbents. Here, a novel superabsorbent was synthesized through grafting of acrylic acid onto collagen in the presence of hydrophobic styrene as co-monomer. Subsequently, the effect of styrene on the swelling behaviour of the superabsorbent was studied. RESULTS: The highly swelling supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 30 publications
0
29
0
1
Order By: Relevance
“…After introducing St, the hydrophobic phenyl rings as pendant groups can not participate in hydrogen bonding, and while causes a steric repulsion among chains in the polymeric network. [24,25,27] This decreases the hydrogen bonding interaction between polymeric chains, restricts the entanglement of hydrophilic polymer chains and expands the hydrophilic network. As a result, the water molecules can more easily penetrate into the network voids and the swelling capacity of the superabsorbent was increased.…”
Section: Influence Of St Concentration On Swelling Capacitymentioning
confidence: 98%
See 2 more Smart Citations
“…After introducing St, the hydrophobic phenyl rings as pendant groups can not participate in hydrogen bonding, and while causes a steric repulsion among chains in the polymeric network. [24,25,27] This decreases the hydrogen bonding interaction between polymeric chains, restricts the entanglement of hydrophilic polymer chains and expands the hydrophilic network. As a result, the water molecules can more easily penetrate into the network voids and the swelling capacity of the superabsorbent was increased.…”
Section: Influence Of St Concentration On Swelling Capacitymentioning
confidence: 98%
“…[24] Measurements of the Equilibrium Swelling Capacity and Swelling Rate 0.05 g (±0.0001 g, m 1 ) of the ground xerogel was immersed in 250 mL distilled water or 0.9 wt% NaCl solution for 3 h to reach swelling equilibrium. The swollen gels were filtered through a 100-mesh sieve, drained for 10 min, spread on tissue paper, and wiped to remove unabsorbed water and excess surface water, and then weighed (m 2 ).…”
Section: Preparation Of Gg-g-p(naa-co-st)/apt Superabsorbent Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, most of the superabsorbents used in practice are petroleum-based synthetic polymer with high production cost and poor environmental friendly properties, 14 and thus new types of multi-component superabsorbents derived from naturally available polysaccharides and facile synthesis methods are desired. [15][16][17][18][19] Semi-interpenetrated polymer network (semi-IPN) is a way of blending two polymers where only one is crosslinked in the presence of the another to produce an additional noncovalent interaction between the two polymers. 20 Semi-IPN is an unique "alloys'' of crosslinked polymers, which has been developed as a convenient technique of preparing multicomponent polymer materials and provided a convenient route to modify the properties of natural polymer-based hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…However, some physical filled APT often blocks some free network voids for holding water. It was reported that the incorporation of the proper amount of hydrophobic segments into the hydrophilic matrix could alter the physical properties and control the hydration and diffusion of the swelling media into the matrix network 30–32. However, so far, few investigations have been done with respect to the effect of inorganic clay and hydrophobic monomer on the swelling properties of the superabsorbents.…”
Section: Introductionmentioning
confidence: 99%